Manufacturing method and manufacturing apparatus for optical components

By directly orienting a polymerizable liquid crystal compound on a transparent base material with UV light, the method simplifies and reduces the cost of manufacturing optical members with retardation layers, addressing the high costs and complexity of conventional methods.

JP7600779B2Active Publication Date: 2024-12-17USHIO INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021037495
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2024-12-17
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Conventional methods for manufacturing optical members with retardation layers are costly due to the use of expensive alignment films and require additional steps like forming and curing an alignment film, which increases manufacturing complexity and costs.

Method used

Irradiate a transparent base material with linearly polarized ultraviolet light of 200 nm or less to directly orient a polymerizable liquid crystal compound, eliminating the need for an alignment film and simplifying the manufacturing process by using materials like PET, TAC, or cyclic olefin polymer.

Benefits of technology

This method reduces manufacturing costs and complexity by eliminating the need for expensive alignment films and additional processing steps, while maintaining the optical properties of the retardation layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600779000001
    Figure 0007600779000001
  • Figure 0007600779000002
    Figure 0007600779000002
  • Figure 0007600779000003
    Figure 0007600779000003
Patent Text Reader

Abstract

To provide a simpler method of manufacturing an optical member having a retardation film.SOLUTION: A method of manufacturing an optical member is provided, the method comprising: preparing a base material that is substantially transparent at a wavelength used by the optical member (S1); irradiating the base material with linearly polarized ultrasonic light of a wavelength of 200 nm or less to apply alignment treatment to the base material (S2); laminating a polymerizable liquid crystal compound on the base material after the alignment treatment (S3); and allowing the polymerizable liquid crystal compound to be aligned according to the state of the base material to form a retardation layer (S3-S5).SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing an optical member having a retardation layer. [Background technology]

[0002] In the field of optics, controlling the phase of light is an important technology. Wave plates such as quarter-wave plates and half-wave plates are widely used as optical components for controlling the phase of light. Wave plates are also called retardation plates, retardation films, or retardation layers.

[0003] For example, LCD displays, by their very nature, require a retardation film to control brightness, while OLED displays require an anti-reflection film to suppress external light reflection, and the anti-reflection film has a laminated structure of a linear polarizer and a quarter-wave plate.

[0004] Retardation plates / retardation films used in applications such as display devices are required to provide a uniform retardation to light in a wide wavelength range. In recent years, in order to meet the demand for thinner optical components, retardation films using polymerizable liquid crystal compounds have been proposed, for example as described in Patent Document 1. As the polymerizable liquid crystal compound, for example, an ultraviolet-curable liquid crystal monomer (UV-curable liquid crystal) that is cured by irradiation with ultraviolet light is used.

[0005] A conventional manufacturing process for a retardation film using a conventional polymerizable liquid crystal compound will be described.

[0006] This production method involves applying a polymerizable composition containing a polymerizable liquid crystal compound onto a support that has been subjected to an alignment treatment, drying the solvent, aligning the liquid crystal compound, and then polymerizing the compound by ultraviolet light or heat.

[0007] FIG. 1 is a cross-sectional view showing a conventional method for manufacturing an optical member 900 including a retardation film.

[0008] As shown in FIG. 1(a), a substrate 902 is prepared to support an alignment film layer and a retardation layer, which will be described later. Next, as shown in FIG. 1(b), an alignment film 904 is applied to the surface of the substrate 902. Then, as shown in FIG. 1(c), an alignment treatment is performed to impart alignment to the alignment film 904. As the alignment treatment, a rubbing method, a photo-alignment method, or the like is used. FIG. 1(c) shows the photo-alignment treatment. That is, the alignment film 904 is irradiated with linearly polarized ultraviolet light to perform the alignment treatment of the alignment film.

[0009] 1(d), a film of a polymerizable liquid crystal compound 906 (for example, an ultraviolet-curable liquid crystal monomer) is formed by coating on the alignment film 904 that has been subjected to the alignment treatment. The polymerizable liquid crystal compound 906 is aligned according to the alignment of the alignment film 904 that is the base.

[0010] Next, as shown in FIG. 1(e), the laminate 910 of the substrate 902, the alignment film 904, and the polymerizable liquid crystal compound 906 produced in FIG. 1(d) is heated. The polymerizable liquid crystal compound 906 is dried and fixed while maintaining its alignment state. Thereafter, as shown in FIG. 1(f), the aligned polymerizable liquid crystal compound 906 is irradiated with ultraviolet light. This heating or UV irradiation hardens and fixes the polymerizable liquid crystal compound. As a result, the hardened polymerizable liquid crystal compound that maintains its alignment state becomes the retardation layer 908.

[0011] Next, as shown in FIG. 1(g), the retardation layer 908 of the laminate 910 is bonded to another optical element 920 (eg, a polarizing film, etc.).

[0012] Subsequently, as shown in FIG. 1( h ), the substrate 902 and the alignment film 904 are peeled off, and the retardation layer 908 is transferred to another optical element 920 .

[0013] For example, when the retardation layer 908 is configured to function as a quarter wave plate and the optical element 920 is a linear polarization element, the optical member 900 can be configured as an anti-reflection film. [Prior art documents] [Patent documents]

[0014] [Patent Document 1] JP 2020-86397 A Summary of the Invention [Problem to be solved by the invention]

[0015] In the conventional manufacturing process for the optical member 900, an alignment film 904 is used as a base to align the polymerizable liquid crystal compound 906.

[0016] The alignment process for the alignment film 904 can be performed using a rubbing method or a photo-alignment method. The photo-alignment method has the following advantages over the rubbing method. Unlike the rubbing method, the photo-alignment method is a non-contact process, so it does not generate dust or static electricity, improving yields. In addition, it is possible to perform alignment process on fine parts that cannot be handled by the rubbing method.

[0017] For this reason, a special film that can be photo-aligned is often used as the alignment film, but the material of the film that can be photo-aligned is expensive, which increases the cost of the optical member 900.

[0018] Furthermore, a step of forming the alignment film 904 on the substrate 902 is required before aligning the polymerizable liquid crystal compound 906, which increases the manufacturing cost.

[0019] The present disclosure has been made in view of the above problems, and an exemplary purpose of an embodiment of the present disclosure is to provide a method for producing an optical member having a retardation film that is simpler than conventional methods. [Means for solving the problem]

[0020] A method for producing an optical member according to an embodiment of the present disclosure includes the steps of irradiating a substrate that is substantially transparent to the wavelength used in the optical member with linearly polarized ultraviolet light having a wavelength of 200 nm or less, and laminating a polymerizable liquid crystal compound on the substrate after irradiation with the linearly polarized ultraviolet light, thereby forming a retardation layer by orienting the polymerizable liquid crystal compound.

[0021] Another aspect of the present disclosure is an apparatus for manufacturing an optical member, comprising: a conveying means for conveying a base material made of a resin other than polycarbonate and substantially transparent to the wavelength used in the optical member; and an illumination device for irradiating the base material with linearly polarized ultraviolet light having a wavelength of 200 nm or less.

[0022] An optical component according to one embodiment includes a substrate made of at least one of PET, TAC, and cyclic olefin polymer (also referred to as COP, COC, or COR), and a polymerizable liquid crystal compound that is directly laminated onto the substrate without any other layer therebetween, and at least a portion of the polymerizable liquid crystal compound is oriented according to the state of the substrate.

[0023] In addition, any combination of the above components, and mutual substitution of the components and expressions of the present disclosure between methods, devices, systems, etc. are also valid aspects of the present disclosure. Effect of the Invention

[0024] According to an embodiment of the present disclosure, an optical member having a retardation layer can be produced more simply than before. [Brief description of the drawings]

[0025] [Figure 1] 1A to 1C are cross-sectional views showing a conventional method for manufacturing an optical member having a retardation film. [Diagram 2] 2(a) to (e) are cross-sectional views illustrating a method for producing an optical member according to an embodiment. [Diagram 3] 2 is a flowchart of a manufacturing method according to an embodiment. [Figure 4] 4(a) to (d) are cross-sectional views illustrating a method for producing an optical member. [Diagram 5] 5(a) and (b) are diagrams showing a liquid crystal cell structure for evaluation including a test film to be evaluated. [Figure 6] FIG. 2 is a cross-sectional view of the evaluation system. [Figure 7] 7(a) and (b) are photographs of the reference test film. [Figure 8] 8(a) to (c) are schematic diagrams of a photo-alignment treatment system that irradiates a test film with polarized ultraviolet light to perform a photo-alignment treatment. [Figure 9] 9(a) to (c) are diagrams showing the emission spectra of a Xe excimer lamp, a KrCl excimer lamp, and a Deep-UV lamp. [Figure 10] FIG. 1 is a diagram showing the extinction ratio and transmittance characteristics of a VUV polarizing plate. [Figure 11] FIG. 1 is a diagram showing the extinction ratio and transmittance characteristics of a DUV polarizing plate. [Figure 12] FIG. 1 shows photographs of samples #11 to #15 using TAC film. [Figure 13] FIG. 1 shows photographs of samples #21 to #27 using a PET film. [Figure 14] FIG. 1 shows photographs of samples #31 to #35 using a COP film. [Figure 15] FIG. 1 shows photographs of samples #41 to #45 using PC film. [Figure 16] FIG. 1 shows photographs of samples #51 to #59 using a PET film and samples #61 to #64 using a PI film. [Figure 17] FIG. 13 is a diagram showing a list of results of samples created using different materials and conditions. [Figure 18] 18(a) and (b) are diagrams showing a manufacturing apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] (Overview of the embodiment) A summary of some exemplary embodiments of the present disclosure will be described. This summary is intended to provide a simplified summary of some concepts of one or more embodiments in order to provide a basic understanding of the embodiments as a prelude to the detailed description that follows, and is not intended to limit the scope of the invention or disclosure. Furthermore, this summary is not intended to be a comprehensive overview of all possible embodiments, nor is it intended to limit essential components of the embodiments. For convenience, the term "one embodiment" may be used to refer to one embodiment (example or variant) or multiple embodiments (examples or variants) disclosed in this specification.

[0027] The inventors focused on the substrate constituting the retardation layer and attempted to perform an alignment treatment to impart alignment to the substrate itself. As a result, it was found that it is possible to directly impart alignment to the substrate itself by irradiating linearly polarized ultraviolet light with a wavelength of 200 nm or less (222 nm or 254 nm depending on the substrate material) for a specific material used in an optical component (e.g., an optical film).

[0028] That is, the inventors have discovered a method for manufacturing an optical component (a method for imparting alignment), which allows a polymerizable liquid crystal compound to be aligned using a substrate as a base without using an alignment film formed on the substrate as a base, and enables a retardation layer made of a cured product of the polymerizable liquid crystal compound in which the aligned state is maintained to be formed on the substrate.

[0029] A method for manufacturing an optical member according to one embodiment includes the steps of irradiating a substrate that is substantially transparent to the wavelength used in the optical member with linearly polarized ultraviolet light having a wavelength of 200 nm or less, laminating a polymerizable liquid crystal compound on the substrate after irradiation with the linearly polarized ultraviolet light, and forming a retardation layer by orienting the polymerizable liquid crystal compound in accordance with the state of the substrate.

[0030] According to this method, the substrate can be oriented by irradiation with linearly polarized ultraviolet light having a wavelength of 200 nm or less. Then, by laminating a polymerizable liquid crystal compound on the oriented substrate as a base, the polymerizable liquid crystal compound can be oriented according to the state of the substrate, and a retardation layer can be formed. This method (i) does not require expensive materials for the orientation film, and (ii) does not require the process of applying and curing the orientation film, so that the process can be simplified and the manufacturing cost can be reduced.

[0031] In one embodiment, since the substrate is transparent, the laminated structure of the substrate and the retardation layer can be used as it is as an optical element. In this case, since there is no need to peel off the substrate, the manufacturing cost can be further reduced.

[0032] In one embodiment, the retardation layer may be aligned in a direction parallel to the polarization direction of linearly polarized ultraviolet light. The material (alignment film) of the photo-alignable film used in the conventional technology is aligned in a direction perpendicular to the polarization direction of linearly polarized ultraviolet light, and the mechanism of the alignment process of the present embodiment is different from that of the conventional material.

[0033] In one embodiment, the photochemical reaction of the substrate induced by irradiation with linearly polarized ultraviolet light may be a decomposition reaction. The material (alignment film) of the photo-alignable film used in the conventional technology utilizes a crosslinking reaction or a polymerization reaction, and the mechanism of the alignment treatment of the present embodiment is different from that of the conventional material.

[0034] In one embodiment, the material of the substrate may be any one of PET (polyethylene terephthalate), TAC (triacetyl cellulose), and cyclic olefin polymer. Since PET and TAC are inexpensive and easily available, the use of these materials allows further cost reduction.

[0035] In one embodiment, the polymerizable liquid crystal compound may have anomalous dispersion, which allows the properties of the optical member to be uniform across the entire visible light range.

[0036] In one embodiment, the irradiation with linearly polarized ultraviolet light may be performed in an inert gas atmosphere.

[0037] In one embodiment, the substrate may be PET. The step of irradiating with linearly polarized ultraviolet light may be performed by irradiating with linearly polarized ultraviolet light having a wavelength of 222 nm or 254 nm instead of linearly polarized ultraviolet light having a wavelength of 200 nm or less.

[0038] In one embodiment, the substrate is PET, and irradiation with linearly polarized ultraviolet light may be performed in an atmosphere containing oxygen.

[0039] An apparatus for manufacturing an optical member according to an embodiment includes a conveying means for conveying a substrate that is substantially transparent to the wavelength used by the optical member, and an illumination device for irradiating the substrate with linearly polarized ultraviolet light having a wavelength of 200 nm or less. The apparatus may further include a coating device for coating a polymerizable liquid crystal compound on the substrate after irradiation with the linearly polarized ultraviolet light.

[0040] The optical member according to one embodiment includes a substrate made of at least one of PET, TAC, and a cyclic olefin polymer, and a polymerizable liquid crystal compound that is directly laminated on the substrate without any other layer, and at least a part of the polymerizable liquid crystal compound is aligned. The molecules that constitute the substrate may be decomposed, not polymerized or crosslinked.

[0041] (Embodiment) Hereinafter, preferred embodiments will be described with reference to the drawings. The same or equivalent components, parts, and processes shown in each drawing will be given the same reference numerals, and duplicated descriptions will be omitted as appropriate. In addition, the embodiments are illustrative and do not limit the disclosure or invention, and all features and combinations thereof described in the embodiments are not necessarily essential to the disclosure or invention.

[0042] In addition, the dimensions (thickness, length, width, etc.) of each component shown in the drawings may be enlarged or reduced as appropriate for ease of understanding. Furthermore, the dimensions of multiple components do not necessarily represent their relative sizes, and even if a component A is drawn thicker than another component B on the drawings, component A may actually be thinner than component B.

[0043] 2(a) to 2(e) are cross-sectional views showing a method for producing an optical member according to an embodiment. Fig. 3 is a flowchart of the production method according to an embodiment.

[0044] As shown in FIG. 2(a), first, a base material 102 for supporting a retardation layer 108 (described later) is prepared (step S1 in FIG. 3).

[0045] The substrate 102 is made of a resin material discovered by the inventors that is given orientation by irradiation with linearly polarized ultraviolet light. Since the substrate 102 is used as a substrate for an optical element, the resin material is preferably a material that is optically transparent to visible light, in particular, a material that is colorless and transparent.

[0046] It is more preferable that the optically alignable transparent substrate 102 has a transmittance in the visible light region of 50% or more, and more preferably 80% or more.

[0047] Next, as shown in FIG. 2(b), the surface of the substrate prepared in process S1 is irradiated with linearly polarized ultraviolet light having a wavelength of 200 nm or less (hereinafter also referred to as linearly polarized vacuum ultraviolet (VUV) light) to perform an alignment process on the substrate 102 (process S2).

[0048] As the ultraviolet light source, for example, a Xe excimer lamp that emits ultraviolet light with a central wavelength of 172 nm can be used. Note that instead of the excimer lamp, an excimer laser with a wavelength of 193 nm can also be used.

[0049] 2(c), a polymerizable liquid crystal compound 106 (for example, an ultraviolet-curable liquid crystal monomer) is applied onto the substrate 102 that has been subjected to the alignment treatment to form a film. Then, the polymerizable liquid crystal compound 106 is aligned by the alignment property of the substrate 102 (process S3).

[0050] 2(d), the laminate 110 of the substrate 102 and the polymerizable liquid crystal compound 106 is heated (step S4). The polymerizable liquid crystal compound 106 is dried and fixed while maintaining the aligned state. The heating means may be appropriately selected from known heating and drying means.

[0051] 2(e), the aligned polymerizable liquid crystal compound 106 is irradiated with ultraviolet light (for example, 365 nm) to polymerize and harden the polymerizable liquid crystal compound 106 (step S5). This results in a retardation layer 108 made of a hardened polymerizable liquid crystal compound that maintains its aligned state.

[0052] In this manner, an optical member (retardation film) 100 is obtained, which is made up of the transparent base material 102 and the retardation layer 108. This optical member 100 may be used as a final product.

[0053] Alternatively, the optical member 100 may be used as an intermediate material (part) of another optical member 200. Figures 4(a) to 4(d) are cross-sectional views showing a manufacturing method of the optical member 200. For example, the retardation layer 108 may be bonded to another optical element to form another optical member 200.

[0054] As shown in Fig. 4(a), the retardation layer 108 of the optical member 100 is bonded to another optical element 120. The state shown in Fig. 4(b) may be the final optical member 200A. Since the base material 102 is transparent, the function of the optical member 200A is not lost even if it is left as it is.

[0055] Alternatively, when a thinner optical member is required, the substrate 102 may be peeled off as shown in FIG. 4(c), and the laminated structure of the retardation layer 108 and the optical element 120 as shown in FIG. 4(d) may be used as the final optical member 200B.

[0056] For example, when the retardation layer 108 is configured to function as a quarter-wave plate, an anti-reflection film can be formed by bonding or transferring this retardation layer 108 to the optical element 120, which is a linear polarizing element.

[0057] The above is the method for producing an optical member according to the embodiment.

[0058] Next, a sample produced using this manufacturing method and its evaluation will be described.

[0059] [Evaluation of photoalignment substrate] First, the evaluation of the orientation induced in the substrate by irradiation with linearly polarized VUV light will be described.

[0060] 1. Rating System The inventors have constructed an evaluation system for evaluating the quality of photo-alignment of a substrate irradiated with linearly polarized VUV light.

[0061] 5(a) and (b) are diagrams showing a liquid crystal cell structure 400 for evaluation including a test film to be evaluated. The test film 300 is a simulation of the substrate 102, and is made of the same material as the substrate 102. A part of the test film 300 (called a photo-aligned region) 302 is aligned by irradiation with linearly polarized VUV light. The remaining part of the test film 300 (called a non-photo-aligned region) 304 is the original resin material that is not irradiated with linearly polarized VUV light, and is a reference region that is not aligned.

[0062] 5(a), in addition to the test film 300, the liquid crystal cell structure 400 includes a TN liquid crystal 410 and an alignment film substrate 420. The alignment film substrate 420 is formed by forming an alignment film 424 on a glass substrate 422. This alignment film 424 is, for example, a polyimide (PI) coating film, and is given alignment by rubbing.

[0063] 5CB (4-pentyl-4'-cyanobiphenyl) liquid crystal is dropped onto this alignment film substrate 420 to form a liquid crystal layer 410, and a base material to be evaluated (test film 300) is laminated on top of it.

[0064] The test film 300 after irradiation with linearly polarized VUV light is given an orientation by the above-mentioned principle. The orientation of the liquid crystal layer 410 changes depending on the orientation state of the test film 300 in contact with it. When the orientation direction of the liquid crystal layer 410 at the interface in contact with the test film 300 is perpendicular to the orientation direction of the orientation film 424 of the orientation film substrate 420 arranged below it, the liquid crystal molecules in the liquid crystal layer 410 are twisted by 90 degrees, and exhibit the action of rotating the polarization direction of polarized light passing through the liquid crystal layer 410 by 90 degrees, and the liquid crystal cell structure 400 becomes a TN type liquid crystal cell structure (hereinafter also referred to as a TN cell structure). The liquid crystal layer 410 simulates the polymerizable liquid crystal compound 106 of the optical member 100.

[0065] 6 is a cross-sectional view of an evaluation system 500. In addition to the liquid crystal cell structure 400, the evaluation system 500 includes a first polarizing film 510, a second polarizing film 520, and a backlight illumination 530. The liquid crystal cell structure 400 is sandwiched between the first polarizing film 510 and the second polarizing film 520.

[0066] The backlight illumination 530 is a tracing table with an internal fluorescent lamp, on which the second polarizing film 520 is placed, and the liquid crystal cell structure 400 is placed on top of the second polarizing film 520. The first polarizing film 510 is placed on top of the liquid crystal cell structure 400. Here, the first polarizing film 510 and the second polarizing film 520 are placed so that their polarization directions are perpendicular to each other (crossed Nicol arrangement).

[0067] If the alignment treatment applied to the photo-alignment region 302 is satisfactory and the liquid crystal cell structure 400 functions as a TN cell structure, the light emitted from the backlight illumination 530 becomes linearly polarized by the second polarizing film 520, and then the polarization direction of the light rotates by 90 degrees as it passes through the liquid crystal cell structure 400 to match the polarization axis direction of the first polarizing film 510, and the light from the backlight illumination 530 (backlight) passes through the first polarizing film 510.

[0068] That is, when the liquid crystal cell structure 400 functions as a TN cell structure, if the orientation regulating force of the photo-alignment region 302 described above is strong and the liquid crystal molecules in the liquid crystal layer 410 are aligned in an orderly manner, when the liquid crystal cell structure 400 is viewed through the first polarizing film 510, the photo-alignment region 302 of the liquid crystal cell structure (TN cell structure) 400 appears white due to the light transmitted from the backlight illumination 530. On the other hand, if the orientation regulating force of the photo-alignment region 302 is weak and the liquid crystal molecules in the liquid crystal layer 410 are not aligned in an orderly manner, when the liquid crystal cell structure 400 is viewed through the first polarizing film 510, the photo-alignment region 302 appears uneven or half-tone, such as liquid crystal drop marks.

[0069] As a reference for the test film (referred to as the reference test film), a sample was prepared by coating a glass substrate with polyimide (PI: Hitachi Chemical's LX-1400) and irradiating the polyimide surface with linearly polarized ultraviolet light having a wavelength of 254 nm from a direction perpendicular to the polyimide surface.

[0070] This sample also has a region that has been subjected to alignment treatment by irradiation with polarized ultraviolet light having a wavelength of 254 nm, and a region that has not been irradiated with polarized ultraviolet light having a wavelength of 254 nm.

[0071] The irradiation direction of the polarized ultraviolet light with a wavelength of 254 nm was perpendicular to the PI film surface.

[0072] A liquid crystal cell (TN cell) shown in FIG. 5(a) was produced using this reference test film, and this liquid crystal cell was placed in the evaluation system shown in FIG.

[0073] 7(a) and (b) are photographs showing the evaluation results of the reference test film. Fig. 7(a) shows a photograph of a first polarizing film 510 overlapping a region of the reference test film that was oriented by irradiation with polarized ultraviolet light having a wavelength of 254 nm, and Fig. 7(b) shows a photograph of a first polarizing film 510 overlapping a region of the reference test film that was not irradiated with polarized ultraviolet light having a wavelength of 254 nm.

[0074] It is generally known that when PI (polyimide) is irradiated with vertically polarized ultraviolet light with a wavelength of 254 nm as described above, the liquid crystal is aligned but does not generate a pretilt angle. The pretilt angle is the angle (rise angle) between the alignment film interface and the liquid crystal molecules in contact with it. In the case of the rubbing method, a pretilt angle is generated by strongly rubbing in a certain direction, and the molecules are aligned in the same direction at the same angle, resulting in a uniform screen without liquid crystal inversion, i.e., disclination (line defect). In the case of the photoalignment method, it is known that irradiation from the vertical direction hardly generates a pretilt angle (i.e., the liquid crystal molecules are aligned almost parallel to the alignment film surface). Therefore, in the photoalignment method, following irradiation from the vertical direction, polarized light is irradiated from an angle with an offset angle from the vertical direction to give anisotropy in the alignment film depth direction, generating a pretilt angle and aligning the rise direction (two-time irradiation method). In the conventional report, in the photo-alignment method of a PI (polyimide) film using DUV polarized light, the alignment direction is perpendicular to the polarization axis, so the first irradiation from the vertical direction is performed by irradiating with DUV polarized light with a polarization axis perpendicular to the direction to be aligned, and the second irradiation to generate a pretilt angle is performed by rotating the polarization axis by 90 degrees from the first irradiation and then tilting it. This is because if the polarization axis is not rotated by 90 degrees, anisotropy in the depth direction cannot be imparted even if the light is tilted (it becomes isotropic), so a pretilt angle cannot be generated. In the examples of the present disclosure, the purpose is to confirm whether or not alignment is imparted, so evaluation is performed with only one irradiation from the vertical direction, and a pretilt angle is not generated. Therefore, when observing FIG. 7(a), disclinations (line defects) are observed (parts that look like black lines), but the light that has passed through the evaluation liquid crystal cell structure 400 and the first polarizing film 510 looks white overall. In other words, it has been confirmed that the reference test film was photo-aligned by irradiation with a wavelength of 254 nm.

[0075] On the other hand, as shown in Fig. 7(b), in the photograph of the area where the PI was not irradiated with the polarized ultraviolet light of 254 nm wavelength, the liquid crystal was left behind and the overall unevenness was observed. This state indicates that the liquid crystal was not aligned in the area where the polarized ultraviolet light of 254 nm wavelength was not irradiated. Note that the alignment film 424 on the glass substrate 422 below the liquid crystal layer 410 shown in Fig. 5(a) was previously given an alignment property by rubbing, so the diagram shown in Fig. 7(b) shows the unevenness caused only by the test film (PI sample) 300 above the liquid crystal layer 410 shown in Fig. 5(a).

[0076] As described above, by observing the test film using the evaluation system shown in FIG. 6, it becomes possible to evaluate the alignment state and alignment control force of the photo-aligned region 302 of the test film.

[0077] 2. Optical Alignment System Next, the apparatus used to prepare the test film will be described.

[0078] 8(a) to (c) are schematic diagrams of a photo-alignment treatment system 600 that performs photo-alignment treatment by irradiating a test film with polarized ultraviolet light. As light sources, a Xe excimer lamp, a KrCl excimer lamp, and a Deep-UV lamp (also called an ultra-high pressure mercury lamp or an ultra-high pressure UV lamp) were used. Fig. 9(a) to (c) are diagrams showing the emission spectra of a Xe excimer lamp, a KrCl excimer lamp, and a Deep-UV lamp.

[0079] The optical alignment treatment system 600A shown in Fig. 8(a) uses an Xe excimer lamp 610a as a light source. As shown in Fig. 9(a), the central wavelength of the light emitted from the Xe excimer lamp 610a is 172 nm.

[0080] Returning to FIG. 8(a), the Xe excimer lamp 610a is disposed in a lamp house 614. A reflecting mirror 612 is provided below the lamp house 614 (the lower side in FIG. 8(a)). Therefore, the light emitted from the Xe excimer lamp 610a travels upward from the lamp house 614 (the direction of the arrow shown in FIG. 8(a)).

[0081] A polarizer for vacuum ultraviolet light (VUV) (hereinafter also referred to as a VUV polarizer) 620a is disposed above the light exit port of the lamp house 614. Fig. 10 is a diagram showing the extinction ratio and transmittance characteristics of the VUV polarizer 620a. In the figure, the solid line indicates the extinction ratio characteristics, and the dashed line indicates the transmittance characteristics.

[0082] In the VUV polarizer 620a used here, the extinction ratio is 16:1 and the transmittance is 16% at the central wavelength of 172 nm of the Xe excimer lamp light (measured value for parallel light). As shown in FIG. 9(a), the wavelength emitted by the Xe excimer lamp 610a spreads to a full width at half maximum of 14 nm, and the spectrum has a slightly long tail on the long wavelength side. The extinction ratio in the wavelength range of 165 to 179 nm, which is the full width at half maximum, is 10:1 to 70:1. Therefore, the average extinction ratio considering the wavelength distribution is about 25:1. Since the Xe excimer lamp is a divergent light, the extinction ratio deteriorates due to the obliquely incident component, so the extinction ratio is about 1 / 5 to about 1 / 10, and is considered to be about 5:1 to about 3:1.

[0083] 8(a), an L-shaped light shielding plate 630 is disposed above the VUV polarizing plate 620a. The L-shaped light shielding plate 630 is an L-shaped angle made of bright aluminum alloy, and has a plate thickness of 0.5 mm.

[0084] The flat portion of the L-shaped light shielding plate 630 covers the area of ​​the test film 300 that should become the non-photo-aligned area 304. Because the light shielding plate 630 blocks the Xe excimer lamp light, the Xe excimer lamp light is not irradiated onto approximately half of the area of ​​the test film 300. As a result, the test film 300 has the photo-aligned area 302 and the non-photo-aligned area 304 as shown in FIG. 5(b).

[0085] The lamp house 614 containing the Xe excimer lamp 610a, the VUV polarizer 620a, and the light shielding plate 630 are disposed in a purge box 640. The purge box 640 contains nitrogen (N 2) gas makes it possible to purge the oxygen concentration in purge box 640 to 0.1% or less.

[0086] The photo-alignment treatment system 600A using the Xe excimer lamp 610a is capable of irradiating the test film 300 with light in both the air atmosphere and the oxygen-purged atmosphere. When irradiating with vacuum ultraviolet light in the air atmosphere, active oxygen and ozone are generated by the photodecomposition reaction of oxygen in the air, resulting in an oxidizing atmosphere.

[0087] The optical alignment treatment system 600B shown in FIG. 8(b) uses a KrCl excimer lamp 610b as a light source.

[0088] The KrCl excimer lamp 610b is disposed in a lamp house 614. A reflecting mirror 612 is provided below the lamp house 614 (the lower side in FIG. 8(b)). Therefore, light emitted from the KrCl excimer lamp 610b travels upward from the lamp house 614 (the direction of the arrow shown in FIG. 8(b)).

[0089] A wavelength-selecting filter 622 is disposed on the upper part of the lamp house 614. Fig. 9(b) shows the spectral distribution of light emitted from a KrCl excimer lamp. In the figure, the dashed line indicates the spectral distribution when the wavelength-selecting filter 622 is not disposed, and the solid line indicates the spectral distribution after transmission through the wavelength-selecting filter 622 when the wavelength-selecting filter 622 is disposed.

[0090] In addition, for both spectral characteristics, the light intensity at the peak wavelength is set to 100 (au). As shown in the figure, the central wavelength of the light emitted from the KrCl excimer lamp is 222 nm. The full width at half maximum is 2 nm, which is a narrower and sharper spectrum than that of the Xe excimer lamp.

[0091] A polarizing plate for deep ultraviolet light (DUV) (hereinafter also referred to as a DUV polarizing plate) 620b is disposed on the light emission surface of the wavelength selection filter 622. Fig. 11 is a diagram showing the extinction ratio and transmittance characteristics of the DUV polarizing plate. In the figure, the solid line shows the extinction ratio characteristics, and the dashed line shows the transmittance characteristics.

[0092] In the DUV polarizer 620b used here, the extinction ratio is 685:1 at the central wavelength of 222 nm of the KrCl excimer lamp light (measured value for parallel light). As mentioned above, the full width at half maximum of the spectrum of the KrCl excimer lamp is narrow at 2 nm, so the extinction ratio does not change significantly in this wavelength range, and the average extinction ratio is about 700:1. Note that since the KrCl excimer lamp is a divergent light source, there is a component that is obliquely incident on the DUV polarizer 620b. Therefore, the actual extinction ratio is slightly worse than the above, and is thought to be about 140:1 to about 70:1. In addition, the transmittance was 23%.

[0093] Returning to Fig. 8(b), an L-shaped light shielding plate 630 is disposed above the DUV polarizing plate 620b, as in Fig. 8(a). This light shielding plate 630 forms photo-aligned regions 302 and non-photo-aligned regions 304 in the test film 300.

[0094] In addition, when the KrCl excimer lamp 610b is used, photolysis of oxygen in the air does not occur and active oxygen and ozone are not generated, so the light irradiation of the test film 300 is performed in an air atmosphere. Therefore, in the photo-alignment treatment system 600B using the KrCl excimer lamp 610b, the purge box 640 is not necessary.

[0095] The optical alignment treatment system 600C shown in Fig. 8(c) uses a deep-UV lamp 610c as a light source. The deep-UV lamp 610c used was a USH-250BY manufactured by Ushio Electric. The deep-UV lamp 610c is mounted on a parallel light irradiation system (Multilight manufactured by Ushio Lighting) 650. The light emitted from the deep-UV lamp 610c travels downward from the parallel light irradiation system 650 (in the direction of the arrow shown in Fig. 8(c)).

[0096] FIG. 9(c) shows the spectral distribution of light emitted from a deep-UV lamp (USH-250BY). As shown in the figure, light of 230 nm or more in the DUV region is emitted from the deep-UV lamp 610c. It is known from past reports that the emission of mercury seen in the range of 230 to 260 nm is effective for PI (polyimide), and the emission in this wavelength range is emission that spreads around the characteristic line of mercury at 254 nm. In this specification, "irradiation with a wavelength of 254 nm" refers to the emission in this range.

[0097] Returning to Fig. 8(c), a DUV polarizer 620c is disposed on the lower side (light irradiation side) of the parallel light irradiation system 650. The DUV polarizer 620c is the same as that used in the optical alignment treatment system 600B shown in Fig. 8(b), and the extinction ratio and transmittance characteristics of the DUV polarizer 620c are shown in Fig. 11.

[0098] In the typical wavelength range of 230 to 260 nm used in conventional photo-alignment treatments, the extinction ratio is approximately 850:1 to 2300:1 (measured with parallel light). The transmittance is 24 to 29%. Note that the light incident from the parallel light irradiation system is parallel light and does not have any obliquely incident components, so the extinction ratio does not deteriorate and the above values ​​can be applied as is.

[0099] Returning to Fig. 8(c), a stage 660 for supporting the test film 300 is provided below the DUV polarizer 620c. The test film 300 is placed on the stage 660, and an L-shaped light shielding plate 630 is placed on the test film 300. The light shielding plate 630 provides the test film 300 with a photo-aligned region 302 and a non-photo-aligned region 304.

[0100] As in the case of using the KrCl excimer lamp 610b, when the deep-UV lamp 610c is used, the light irradiation to the test film 300 is performed in an air atmosphere. Therefore, in the photo-alignment treatment system 600C using the deep-UV lamp 610c, the purge box 640 is not used.

[0101] 〔experiment〕 Photo-alignment was performed using photo-alignment treatment systems 600A to 600C for several different materials, and test film 300 samples were created and evaluated. ·TAC (Triacetylcellulose) ·PET (polyethylene terephthalate) ·COP (Cyclo-Olefin Polymer) · PC (polycarbonate) · PI (polyimide) film

[0102] 1. Experiments using TAC film 1.1 Sample preparation conditions Using the TAC film, several samples (hereinafter referred to as samples #11 to #15) were prepared. Film material: TAC (Triacetylcellulose), thickness 60 μm. (TacBright Optronics Corporation)

[0103] In samples #11 to #14, the TAC film was irradiated with linearly polarized ultraviolet light using a photoalignment system 600A shown in Fig. 8(a). That is, light emitted from a Xe excimer lamp (hereinafter also referred to as 172 nm light) was linearly polarized via a VUV polarizer and irradiated onto half of the area of ​​the TAC film.

[0104] Samples #11 to #14 were irradiated under different conditions. For samples #11 and #12, the TAC film was irradiated with 172 nm polarized VUV light in the air. For samples #13 and #14, the TAC film was irradiated with 172 nm polarized VUV light in the air. 2 The experiment was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0105] Samples #11 and #12 had different irradiation doses. Sample #11 had an irradiation dose of 1 J / cm 2 and for sample #12, 5 J / cm 2 Similarly, samples #13 and #14 had different irradiation doses. Sample #13 had an irradiation dose of 1 J / cm 2 and for sample #14, 5 J / cm 2 It is.

[0106] Sample #15 for comparison was prepared simply by rubbing, not by light irradiation. Rubbing was performed using cellulose (cupra) fiber (Bencotto (trademark): manufactured by Asahi Kasei). Specifically, rubbing was performed by rubbing the TAC film surface in one direction using the Bencotto. As with samples #11 to #14, sample #15 was also subjected to rubbing treatment on only half of the film surface.

[0107] 1.2 Evaluation results of samples #11 to #15 The photoalignment states of Samples #11 to #15 were evaluated using the above-mentioned evaluation system 500. Specifically, a liquid crystal cell structure 400 shown in Fig. 5(a) was produced using each sample of the test film 300, and this liquid crystal cell structure 400 was evaluated using the evaluation system 500 in Fig. 6.

[0108] FIG. 12 is a diagram showing photographs illustrating the evaluation results of samples #11 to #15 using the TAC film.

[0109] The photograph in the figure was taken of the first polarizing film 510 of the evaluation system 500, with the liquid crystal cell structure 400 arranged in two different orientations in the evaluation system 500. The polarization axis direction in Fig. 12 is the polarization axis direction of the polarized VUV light irradiated onto the test film 300, and indicates the orientation in which the liquid crystal cell structure 400 is arranged. For samples #11 to #14, the black frames added to the photographs indicate the photo-aligned regions 302 of the test film 300.

[0110] The polarization direction of the second polarizing film 520 of the evaluation system 500 is the vertical direction on the page in Fig. 12, and the polarization direction of the first polarizing film 510 is the horizontal direction on the page in Fig. 12. When the liquid crystal cell structure 400 functions as a TN cell structure, when the orientation direction of the liquid crystal at the interface between the test film 300 and the liquid crystal layer 410 (hereinafter simply referred to as the orientation direction of the liquid crystal layer 410) is the horizontal direction on the page, the light of the backlight illumination 530 passes through the first polarizing film 510 and appears white in the photograph.

[0111] [Sample#15] The portion enclosed in a black frame for comparative sample #15 indicates the area where the test film 300 was subjected to rubbing treatment. In comparative test sample #15, which was subjected to simple rubbing, the alignment direction of the liquid crystal layer 410 is the same as the rubbing direction. Since the polarization direction of the second polarizing film 520 in the evaluation system 500 is the vertical direction on the page and the polarization direction of the first polarizing film 510 is the horizontal direction on the page, when the liquid crystal cell structure 400 is arranged so that the rubbing direction of the test film 300 of sample #15 is the horizontal direction on the page, the inside of the black frame in the photograph appears white.

[0112] [Sample #11] When a photo-alignment process is performed by irradiating a TAC film with 172 nm polarized VUV light in the atmosphere, the irradiation dose of the 172 nm light (linearly polarized VUV light) is 1 J / cm 2 It was observed that the TAC film was given an orientation when the liquid crystal cell structure was arranged so that the polarization axis direction of the polarized VUV light irradiated to the TAC film was the vertical direction of the paper, whereas the photo-alignment region 302 in the black frame appeared black when the liquid crystal cell structure was arranged so that the polarization axis direction of the polarized VUV light irradiated to the TAC film was the horizontal direction of the paper. Thus, it can be seen that the TAC film was given an orientation by irradiation with 172 nm polarized VUV light, and the liquid crystal layer 410 was oriented according to the orientation of the TAC film. Since some unevenness was observed, it is presumed that the orientation control force was relatively weak.

[0113] Here, when the rubbing direction of the alignment film substrate 420 of the liquid crystal cell structure 400 is perpendicular to the polarization axis direction of the 172 nm polarized VUV light irradiated to the TAC film, the black framed area in Fig. 12 appears white. Since the second polarizing film 520 and the first polarizing film 510 are in a cross-Nicol arrangement, it can be seen that the alignment direction of the liquid crystal layer 410 associated with the alignment property imparted to the TAC film is the left-right direction on the paper. In other words, the liquid crystal layer 410 is oriented in a direction parallel to the polarization axis direction of the 172 nm polarized VUV light irradiated to the TAC film.

[0114] In this embodiment, when the resin substrate 102 undergoing the photo-alignment treatment is irradiated with linearly polarized VUV light, alignment is imparted by a decomposition reaction caused by photoactivity. In a conventional report on a photo-alignment method using deep ultraviolet light with a wavelength longer than 200 nm, it has been said that in the case of such decomposition-type materials, the liquid crystal is oriented in a direction perpendicular to the polarization axis direction of the linearly polarized ultraviolet light irradiated to the alignment film.

[0115] In contrast, in the TAC film of sample #11, the liquid crystals were oriented in a direction parallel to the polarization axis direction of the linearly polarized VUV light irradiated onto the test film 300, and it was confirmed that the film exhibited orientation characteristics different from those of the conventional photo-alignment method using deep ultraviolet light.

[0116] [Sample#12] The irradiation dose at a wavelength of 172 nm is 5 J / cm 2 When the liquid crystal cell structure is oriented such that the polarization axis of the polarized ultraviolet light irradiated onto the TAC film is oriented vertically or horizontally on the page, the black framed area in Figure 12 appears dark. Therefore, at first glance, it does not appear that the TAC film has been given any orientation.

[0117] Here, the inventor hypothesized that when the amount of irradiation with 172 nm light (linearly polarized ultraviolet light) in the atmosphere increases, vertical alignment (VA) is imparted due to the effect of oxidation of the TAC film surface.

[0118] Therefore, in the TN cell structure, instead of the TAC film, a glass substrate with a VA alignment film was taken out of the VA type liquid crystal cell, and this glass substrate with a VA alignment film (hereinafter referred to as VA glass substrate) was placed in place of the test film (TAC) and evaluated. The photograph in the column labeled VA glass substrate in FIG. 12 shows the results. Regardless of the orientation in which the TN cell structure with this VA glass substrate is placed in the evaluation system 500, the first polarizing film 510 appears almost uniformly black. This suggests that when the amount of irradiation of the TAC film in the atmosphere increases (when the film is overexposed), the TAC film may be in a vertical alignment state due to the influence of oxidation.

[0119] [Samples #13 and #14] N 2 When linearly polarized ultraviolet light of 172 nm is irradiated onto a TAC film in a purged atmosphere (oxygen concentration of 0.1% or less), the irradiation dose of the 172 nm light (linearly polarized ultraviolet light) is 1 J / cm 2 In the case of 5J / cm 2 It was also observed that the TAC film had an orientation property.

[0120] Irradiation with 172 nm light (linearly polarized ultraviolet light) in air and N 2 When compared with irradiation with 172 nm light (linearly polarized ultraviolet light) in a purged atmosphere (oxygen concentration 0.1% or less), the irradiation dose of 172 nm light (linearly polarized ultraviolet light) is 5 J / cm 2 In the case of samples #12 and #14, no orientation was observed in the TAC film in air (sample #12). 2 In a purged atmosphere (oxygen concentration 0.1% or less), the provision of orientation was observed (#14). This indicates that oxygen acts to inhibit the provision of orientation by irradiation with 172 nm light (linearly polarized ultraviolet light).

[0121] In addition, N 2 The irradiation dose of 172 nm light (linearly polarized VUV light) in a purged atmosphere is 1 J / cm 2 to 5J / cm 2Although the alignment of the liquid crystal was improved, no significant change was observed. In addition, although it was confirmed that the TAC film had an alignment property, the photograph showed areas corresponding to the droplet marks of the liquid crystal, so the alignment control force was generally considered to be weak.

[0122] In addition, the photograph of the area of ​​the TAC film that was not irradiated with 172 nm light (linearly polarized VUV light) (area not shown in a black frame) shows a change in color due to the orientation of the liquid crystal cell structure. This is thought to be because the stretching process during the TAC film manufacturing process causes some of the molecules that make up the TAC film to face in one direction, giving them a weak orientation, as seen in stretched films. Similar trends are observed in other test films shown later.

[0123] In the case of the TAC film, the black and white are inverted between the areas irradiated with 172 nm light (linearly polarized VUV light) and the areas not irradiated with it. This is thought to be because the orientation of the TAC film is overwritten by the 172 nm light (linearly polarized VUV light).

[0124] 2. Experiments using PET film 2.1 Sample preparation conditions Several samples (hereinafter referred to as samples #21 to #27) were prepared using PET films. Film material: PET (polyethylene terephthalate), thickness 100μm. (Manufactured by Shanghai Plastech International Trading Co., Ltd.)

[0125] In Samples #21 to #26, the PET film was irradiated with linearly polarized ultraviolet light using a photo-alignment treatment system 600A shown in FIG. 8(a).

[0126] Samples #21 to #26 were irradiated under different conditions. For samples #21 to #24, the PET film was irradiated with 172 nm polarized VUV light in the air. For samples #25 and #26, the PET film was irradiated with 172 nm polarized VUV light in the air. 2 The experiment was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0127] Samples #21 to #24 have different irradiation doses, each of which is 0.1 J / cm 2 ,0.2J / cm 2 ,1J / cm 2 ,5J / cm 2 The irradiation dose for samples #25 and #26 was 1 J / cm. 2 and 5 J / cm 2 It is.

[0128] Sample #27 for comparison was prepared simply by rubbing, not by light irradiation. The rubbing method was the same as for sample #15. As with samples #21 to #26, sample #27 was also subjected to rubbing treatment on only half of the film surface.

[0129] 2.2 Evaluation results of samples #21 to #27 The photoalignment states of Samples #21 to #27 were evaluated using the above-mentioned evaluation system 500. The evaluation method was the same as that for Samples #11 to #15.

[0130] FIG. 13 is a diagram showing photographs illustrating the evaluation results of samples #21 to #27 using a PET film.

[0131] [Samples #21-#26] In the case of samples #21 to #26 made of PET, even when irradiated with 172 nm polarized ultraviolet light in air (#21 to #24), the N 2 Even when irradiated with polarized ultraviolet light of 172 nm in a purged atmosphere (oxygen concentration 0.1% or less) (#25, #26), the test film (PET) was given orientation.

[0132] That is, when the liquid crystal cell structure 400 is oriented so that the polarization axis direction of the polarized ultraviolet light irradiated onto the PET film is the vertical direction on the page, the black framed part in Fig. 13 appears black, but when the liquid crystal cell structure 400 is oriented so that the polarization axis direction of the polarized ultraviolet light irradiated onto the PET film is the horizontal direction on the page, the black framed part in Fig. 13 appears white. Therefore, it can be seen that the irradiation of 172 nm polarized ultraviolet light imparts orientation to the PET film, and the liquid crystal is oriented in accordance with the orientation of the PET film.

[0133] In addition, the white-looking area in the black frame in Figure 13 is almost uniformly white, indicating that the alignment of the liquid crystal is good and that the irradiation dose of 172 nm light (linearly polarized ultraviolet light) in the atmosphere is 0.2 mJ / cm 2 At this level, the film is nearly saturated and is comparable to the rubbed sample #27 for comparison.

[0134] Here, the orientation of the PET film by irradiation with 172 nm light (linearly polarized ultraviolet light) was not affected by oxygen, unlike the case of the TAC film. 2 Even in a purged atmosphere (oxygen concentration 0.1% or less), the alignment of the liquid crystal is only achieved when the irradiation dose of 172 nm light (linearly polarized ultraviolet light) is 0.2 mJ / cm 2 It is considered that the flow is nearly saturated at this point.

[0135] In the case of the PET film, as in the case of the TAC film, the liquid crystals are oriented in a direction parallel to the polarization axis of the linearly polarized VUV light irradiated onto the test film.

[0136] In the case of the PET film, the orientation is stronger in the areas that are not irradiated with 172 nm light (linearly polarized ultraviolet light) (areas not shown in black frames) compared to the TAC film. In this case, the orientation direction of the liquid crystals due to the influence of the pulling process during the PET film manufacturing stage is the same as the orientation direction of the liquid crystals in the areas irradiated with 172 nm light (linearly polarized ultraviolet light) (areas shown in black frames).

[0137] Although it is difficult to see in the photograph shown in Figure 13, when the photograph is enlarged, it can be seen that the area irradiated with 172 nm wavelength light (linearly polarized VUV light) (area indicated by a black frame) has a stronger liquid crystal regulating force than the area not irradiated with 172 nm wavelength light (linearly polarized VUV light) (area outside the black frame). Also, when the irradiation dose of 172 nm wavelength light (linearly polarized VUV light) was 0.2 mJ / cm 2 In the above cases, no traces of liquid crystal droplets are visible in the areas indicated by the black frames.

[0138] 3. Experiments using COP films 3.1 Sample preparation conditions Several samples (hereinafter referred to as samples #31 to #35) were prepared using the COP film. Film material: COP (Cyclo-Olefin Polymer), thickness 100 μm. (Manufactured by Zeon Corporation)

[0139] In the samples #31 to #34, the COP film was irradiated with linearly polarized ultraviolet light using a photo-alignment treatment system 600A shown in FIG. 8(a).

[0140] The irradiation conditions for samples #31 to #34 were different. For samples #31 and #32, the COP film was irradiated with 172 nm polarized VUV light in the air. For samples #33 and #34, the COP film was irradiated with N 2 The experiment was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0141] Samples #31 and #32 were irradiated with different amounts of radiation, 1 J / cm 2 and 5 J / cm 2 The irradiation dose for samples #33 and #34 was 1 J / cm. 2 and 5 J / cm 2 It is.

[0142] For comparison, sample #35 was prepared by rubbing instead of light irradiation. The rubbing method was the same as for samples #15 and #27, and only half of the film surface was rubbed.

[0143] 3.2 Evaluation results of samples #31 to #35 The photoalignment states of Samples #31 to #35 were evaluated using the above-mentioned evaluation system 500. The evaluation method was the same as that for Samples #11 to #15.

[0144] FIG. 14 shows photographs of samples #31 to #35 using COP films.

[0145] [Sample #31, #32] When a photo-alignment process is performed by irradiating a COP film with 172 nm polarized ultraviolet light in the atmosphere, the irradiation dose of the 172 nm light (linearly polarized ultraviolet light) is 1 J / cm 2 Although it was observed that sample #31 had a certain degree of orientation, the quality of the orientation was clearly not as good as that of sample #35 for comparison, which had been rubbed, and the orientation control force was weaker than that of the TAC film. 2 In sample #32, almost no orientation was observed, and the vertical orientation as in the case of the TAC film was not suggested.

[0146] [Sample #33, #34] N 2 When irradiated with 172 nm linearly polarized ultraviolet light in a purged atmosphere (oxygen concentration 0.1% or less), the irradiation dose is 1 J / cm 2 Sample #33 is also 5J / cm 2 In sample #34, it was also observed that the orientation was imparted to the COP film, although the orientation control force was weak.

[0147] That is, when the liquid crystal cell structure is oriented so that the polarization axis direction of the polarized ultraviolet light irradiated onto the COP film is the vertical direction on the page, the black framed area in Fig. 14 appears black, but when the liquid crystal cell structure is oriented so that the polarization axis direction of the polarized ultraviolet light irradiated onto the COP film is the horizontal direction on the page, the black framed area in Fig. 14 appears white. This shows that the irradiation of 172 nm polarized ultraviolet light imparts orientation to the COP film, and the liquid crystal is oriented in accordance with the orientation of the COP film.

[0148] As described above, in the case of the COP film, as in the case of the TAC film, irradiation with 172 nm linearly polarized ultraviolet light in air is more effective than irradiation with N 2 The state of orientation imparted to the COP film was not as good as when it was irradiated with 172 nm linearly polarized ultraviolet light in a purged atmosphere, so it is believed that oxygen acts to inhibit the imparting of orientation by irradiation with 172 nm light (linearly polarized ultraviolet light).

[0149] However, although it is observed that alignment is imparted by irradiation with 172 nm linearly polarized ultraviolet light in the black framed area in Figure 14, droplet marks of liquid crystal are also observed. This shows that the alignment control force for the liquid crystal is not sufficient, and the alignment is inferior to that of the TAC film.

[0150] In the COP film, as in the TAC film and PET film, the liquid crystal is also oriented in a direction parallel to the polarization axis direction of the linearly polarized VUV light irradiated onto the test film.

[0151] In addition, in the case of the COP film, compared to the TAC film and PET film, no orientation was observed in the areas that were not irradiated with 172 nm light (linearly polarized ultraviolet light) (areas not shown in black frames). Therefore, in the case of the COP film, the material itself is considered to be in a state close to that of glass, where the orientation direction is random.

[0152] 4. Experiments using PC film 4.1 Sample preparation conditions Several samples (hereinafter referred to as samples #41 to #45) were prepared using the PC film. Film material: PC (polycarbonate), thickness 100 μm. (Mitsubishi Engineering Plastics Corporation)

[0153] In Samples #41 to #44, the PC film was irradiated with linearly polarized ultraviolet light using a photo-alignment treatment system 600A shown in FIG. 8(a).

[0154] Samples #41 to #44 were irradiated under different conditions. For samples #41 and #42, the polarized VUV irradiation of 172 nm light on the PC film was performed in the air. For samples #43 and #44, the irradiation was performed in the N 2 The experiment was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0155] Samples #41 and #42 were irradiated with different amounts of radiation, 1 J / cm 2 and 5 J / cm 2 The irradiation dose for samples #43 and #44 was 1 J / cm. 2 and 5 J / cm 2 It is.

[0156] For comparison, sample #45 was prepared by rubbing instead of light irradiation. The rubbing method was the same as for samples #15 and #27, and only half of the film surface was rubbed.

[0157] 4.2 Evaluation results of samples #41 to #45 The photoalignment states of Samples #41 to #45 were evaluated using the above-mentioned evaluation system 500. The evaluation method was as described above.

[0158] FIG. 15 shows photographs of samples #41 to #45 using PC films.

[0159] [Sample #45] In comparative test sample #45, which underwent simple rubbing, the rubbing direction of second polarizing film 520 was vertical on the page, so when liquid crystal cell structure 400 was positioned so that the rubbing direction of sample #45 was horizontal on the page, the black frame area of ​​the photograph appeared somewhat white.

[0160] [Sample #41, #42] When a photo-alignment process is performed by irradiating a PC film with 172 nm polarized ultraviolet light in the atmosphere, the irradiation dose of the 172 nm light (linearly polarized ultraviolet light) is 1 J / cm 2 Sample #41 is 5 J / cm 2 In neither case of Sample #42, no orientation was imparted to the PC film.

[0161] [Sample #43, #44] On the other hand, N 2 When linearly polarized ultraviolet light of 172 nm is irradiated onto a PC film in a purged atmosphere (oxygen concentration of 0.1% or less), the irradiation dose of the 172 nm light (linearly polarized ultraviolet light) is 1 J / cm 2 Sample #43 is 5 J / cm 2 For sample #44, when compared with the areas corresponding to the areas not irradiated with 172 nm linear polarized ultraviolet light, some changes are observed, but it is difficult to say that orientation has been imparted.

[0162] In addition, when looking at sample #45, which was a PC film subjected to rubbing treatment, the alignment of the liquid crystal in the rubbed area was not good. Therefore, it is considered that it is difficult to impart alignment to the PC film by either rubbing treatment or photo-alignment treatment.

[0163] 5. Wavelength Dependence Experiment Among films made from a number of different materials, PET film showed the best results in terms of the alignment imparted by irradiation with 172 nm polarized ultraviolet light. An experiment was carried out to examine the wavelength dependence of the irradiated light (polarized ultraviolet light). For comparison, the wavelength dependence was also examined for polyimide (PI).

[0164] 5.1 Sample preparation conditions Several samples (hereinafter referred to as samples #51 to #59 and #61 to #64) were prepared using PET film and PI film.

[0165] [Sample #51~#59] The materials for samples #51 to #59 are as follows: Film material: PET (polyethylene terephthalate), thickness 100μm. (Manufactured by Shanghai Plastech International Trading Co., Ltd.)

[0166] For samples #51, #52, #55, and #56, the PET film was irradiated with linearly polarized ultraviolet light using the photoalignment system 600A shown in FIG. 8(a). For samples #51 and #55, irradiation was performed in the air, and for samples #52 and #56, irradiation was performed in N 2 The test was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0167] In addition, for samples #53 and #57, the PET film was irradiated with deep ultraviolet (DUV) light having a central wavelength of 222 nm, and the DUV light irradiation was performed using the optical alignment treatment system 600B of FIG. 8(b).

[0168] In addition, for samples #54 and #58, the PET film was irradiated with deep ultraviolet (DUV) light having a wavelength of 254 nm or more, and the irradiation with DUV light was performed using the optical alignment treatment system 600C shown in FIG. 8(c).

[0169] The irradiation dose for samples #51 to #54 was 1 J / cm 2 The irradiation dose for samples #55 to #58 was 5 J / cm 2 It is.

[0170] Sample #59 was a comparative test film, a PC film that had been simply rubbed.

[0171] [Sample #61~#64] The materials for samples #61 to #64 are as follows: ·PI (polyimide) film···Deposited on a glass substrate. (PI film is manufactured by Hitachi Chemical Co., Ltd.)

[0172] In samples #61 to #64, a glass substrate (not subjected to rubbing treatment) having a PI film formed as an alignment film was used.

[0173] For samples #61 and #62, the PET film was irradiated with linearly polarized ultraviolet light using the photoalignment system 600A shown in FIG. 8(a). For sample #61, irradiation was performed in the air, and for sample #62, irradiation was performed in N 2 The test was carried out in a purged atmosphere (oxygen concentration 0.1% or less).

[0174] For sample #63, the PET film was irradiated with deep ultraviolet (DUV) light with a central wavelength of 222 nm, and the DUV light irradiation was performed using the optical alignment processing system 600B in Fig. 8(b). For sample #64, the deep ultraviolet (DUV) light with a wavelength of 254 nm was irradiated, and the PET film was irradiated with linearly polarized ultraviolet light using the optical alignment processing system 600C in Fig. 8(c).

[0175] The irradiation dose for samples #61 to #64 was 1 J / cm 2 It is.

[0176] 5.2 Wavelength Dependence Evaluation Results The evaluation system 500 described above was used to evaluate samples #51 to #59 and #61 to #64. The evaluation method was as described above, but the orientation of the liquid crystal cell structure 400 including samples #51 to #58 was fixed so that the polarization axis direction of the polarized ultraviolet light irradiated onto the film was the left-right direction of the paper, and images were taken. Sample #59 was also photographed only when the direction of the simple rubbing applied to the PET film was the left-right direction of the paper. The orientation of the liquid crystal cell structure 400 including samples #61 to #64 was fixed so that the polarization axis direction of the polarized ultraviolet light irradiated onto the film was the up-down direction of the paper, and images were taken.

[0177] FIG. 16 shows photographs of samples #51 to #59 using a PET film and samples #61 to #64 using a PI film.

[0178] [Sample #61~#64] In the case of a glass substrate with a PI alignment film, previous reports have shown that when the PI alignment film is irradiated with linearly polarized DUV light, the PI decomposition reaction imparts alignment to the PI alignment film, and liquid crystals are oriented in a direction perpendicular to the polarization axis direction of the linearly polarized DUV light.

[0179] Therefore, by orienting the liquid crystal cell structure 400 as described above, the liquid crystal cell structure 400 in the evaluation system 500 functions as a TN cell structure, and the light from the backlight illumination 530 passes through the area of ​​the PI film surrounded by a black frame shown in Figure 16, appearing white in the figure.

[0180] [Sample #51~#58] For PET film, air and N 2The PET film was oriented when irradiated with polarized UV light of 172 nm, 222 nm, or 254 nm in a purged atmosphere (oxygen concentration 0.1% or less). In particular, the PET film was oriented most favorably when irradiated with polarized UV light of 172 nm. Furthermore, the orientation direction imparted to the PET film was parallel to the polarization axis, regardless of the wavelength. The orientation direction was the same with DUV light as with VUV light, which is different from the previously reported results of orthogonal to the DUV polarization axis in PI films. This indicates that, whereas conventional methods of imparting orthogonal orientation to PI (polyimide) using DUV polarized light required two irradiations to generate a pretilt angle, this time it was possible to simultaneously generate both orientation and a pretilt angle with a single tilted irradiation.

[0181] [Sample #61~#64] On the other hand, in the case of glass substrates with a PI alignment film, alignment was imparted to the PI film in both sample #63, which was irradiated with polarized UV light at a wavelength of 222 nm, and sample #64, which was irradiated with polarized UV light at a wavelength of 254 nm. In particular, the alignment of the PI alignment film was more favorable in sample #63, which was irradiated with polarized UV light at a wavelength of 222 nm. In this case, the alignment direction was orthogonal, as reported previously for 254 nm polarized light. On the other hand, when 172 nm polarized UV light was irradiated in air and N 2 No orientation was imparted to samples #61 and #62, which were irradiated in a purged atmosphere (oxygen concentration 0.1% or less).

[0182] This suggests that in the case of a glass substrate with a PI orientation film, there may be a difference in the orientation reaction (decomposition reaction) when it is irradiated with polarized UV light with a wavelength of 172 nm, and when it is irradiated with polarized UV light with a wavelength of 222 nm, or with polarized UV light with a wavelength of 254 nm. Although the reason for this difference is not entirely clear, it is thought that in the case of a PI orientation film, the photon energy of polarized UV light with a wavelength of 172 nm is too large to be contained by cutting specific parts of the PI main chain, and so it may have become disorganized and fall apart.

[0183] 6. Summary FIG. 17 shows a list of the results of samples made with different materials and conditions. As mentioned above, it was found that it is possible to impart orientation to the substrate itself by irradiating it with linearly polarized ultraviolet light with a wavelength of 200 nm or less (172 nm). In the figure, the states of orientation are labeled A, B, C, and D in order from best to worst.

[0184] The degree of orientation is highly dependent on the material of the substrate. The order of best orientation (best orientation control strength, best sensitivity) is PET, TAC, COP, with PET having the best orientation state, orientation control strength, and sensitivity to irradiated linearly polarized ultraviolet light, with an irradiation dose (accumulated light amount) of 0.2 J / cm for linearly polarized ultraviolet light with a wavelength of 172 nm. 2 It was found that the above procedure provided good orientation.

[0185] It was also found that PET was not affected by oxygen when irradiated with polarized ultraviolet light.

[0186] On the other hand, it was found that TAC and COP are affected by oxygen when irradiated with polarized ultraviolet light. In the case of TAC, if the irradiation dose of polarized ultraviolet light with a wavelength of 172 nm is too high (for example, 5 J / cm2) in the air atmosphere (oxygen-containing atmosphere), 2 ), no orientation was imparted. In the case of COP, when irradiated with polarized ultraviolet light with a wavelength of 172 nm, N 2 It was found that a purged atmosphere (oxygen concentration 0.1% or less) was essential. In addition, compared to PET, the state of imparting orientation by irradiation with linearly polarized ultraviolet light with a wavelength of 200 nm or less (wavelength 172 nm) was not good for both TAC and COP. In other words, the orientation control force was weaker than that of PET, and unevenness was noticeable.

[0187] In addition, in the case of a PC, linearly polarized ultraviolet light with a wavelength of 200 nm or less (wavelength 172 nm) was used in air and N 2 Even when irradiated in a purged atmosphere (oxygen concentration 0.1% or less), no orientation was imparted.

[0188] Furthermore, when the wavelength dependency of polarized UV light was investigated for PET, which had the best state of alignment, and a glass substrate with a PI film applied as an alignment film as a reference, it was found that in the case of PET, alignment was imparted with both polarized UV light of 222 nm wavelength and polarized UV light of 254 nm wavelength. In addition, in the case of PET, the shorter the wavelength, the better the alignment was imparted, and the higher the sensitivity to polarized UV light.

[0189] On the other hand, in the case of the reference PI film (not subjected to rubbing treatment), no orientation was imparted when the wavelength of the irradiated polarized ultraviolet light was 200 nm or less (wavelength 172 nm).

[0190] When the wavelengths were 222 nm and 254 nm, the PI film was oriented. In particular, when the PI film was irradiated with polarized UV light with a wavelength of 222 nm, the PI film was better oriented and had high sensitivity to polarized UV light.

[0191] What is noteworthy about the irradiation of polarized UV light onto the substrates in this study is that in the case of a PI film (alignment film) in which alignment is imparted by a photodecomposition reaction, the alignment direction of the liquid crystal is perpendicular to the polarization axis of the polarized UV light irradiated onto the PI film, whereas in the case of the substrates in this study (PET, TAC, COP), the alignment direction of the liquid crystal is parallel to the polarization axis of the polarized UV light irradiated onto each substrate.

[0192] It has now been discovered for the first time that, unlike conventional photo-alignment treatments of PI films, the mechanism by which alignment is imparted may be different (the locations of the main chain, etc. that are cut in the decomposition reaction due to irradiation with polarized ultraviolet light may be different).

[0193] Controlling the pretilt angle of liquid crystals is important for constructing optical films. In conventional Deep-UV light (e.g., 254 nm) decomposition type photoalignment treatments, the liquid crystals are aligned perpendicular to the polarization axis of the polarized ultraviolet light, so after the first irradiation with Deep-UV polarized ultraviolet light, it is necessary to change the direction of the polarization axis by 90 degrees and the incidence angle and irradiate with Deep-UV polarized ultraviolet light a second time.

[0194] In the case of the substrate used in this study, when it is irradiated with polarized ultraviolet light (especially with a wavelength of 200 nm or less), the liquid crystals are oriented parallel to the polarization axis of the polarized ultraviolet light, so that even when controlling the pretilt angle as described above, it is sufficient to irradiate the polarized ultraviolet light only once. This simplifies the manufacturing process and allows optical elements to be manufactured at low cost.

[0195] Next, a manufacturing apparatus that can be used to manufacture the optical member 100 will be described. Figures 18(a) and (b) are diagrams showing a manufacturing apparatus 800. The manufacturing apparatus 800 in Figure 18(a) includes a conveying means 810 and an illumination device 820. The conveying means 810 conveys a workpiece W1 that corresponds to the base material 102 that is substantially transparent to the wavelength used by the optical member 100. The workpiece W1 is wound in a roll, and is pulled out from a feed roller R1 and wound up by a take-up roller R2 while being conveyed.

[0196] The illumination device 820 irradiates the workpiece W1 passing directly below it with linearly polarized ultraviolet light having a wavelength of 200 nm or less (or a wavelength of 222 nm, or a wavelength of 254 nm). The illumination device 820 can use the light sources shown in Figures 8(a) to (c).

[0197] 18(b), a conveying means 810 conveys a workpiece W2, which is a plate-shaped substrate 102. The conveying means 810 is a belt conveyor or a stage. The lighting device 820 emits light when the workpiece W2 passes directly below it, and irradiates the workpiece W2 with linearly polarized ultraviolet light.

[0198] 18(a) and 18(b), the workpieces W1 and W2 processed by the manufacturing apparatus 800 are subjected to a subsequent process. In the subsequent process, a polymerizable liquid crystal compound 106 is applied onto the workpieces by an application means.

[0199] The embodiments merely illustrate the principles and applications of the present invention, and many modifications and changes in arrangement are permitted to the embodiments without departing from the spirit of the present invention defined in the claims.

[0200] According to the present disclosure, instead of providing an alignment property to an alignment film by applying the alignment film to a substrate as in the conventional method, it is possible to provide an alignment property to the substrate itself. Therefore, it is possible to eliminate the alignment film application process from the manufacturing process of the optical member, thereby reducing the manufacturing time and manufacturing costs.

[0201] Furthermore, since no alignment film is required in the manufacturing process, there is no need to use organic compounds to form the alignment film, making it possible to realize a clean manufacturing process for optical members and reducing the burden on the environment.

[0202] This corresponds to Goal 9 of the United Nations Sustainable Development Goals (SDGs) "Build resilient infrastructure, promote inclusive and sustainable industrialization and foster innovation," and also significantly contributes to Target 9.4, which states, "By 2030, improve infrastructure and industry to make them sustainable, through increased resource-use efficiency and greater adoption of clean and environmentally friendly technologies and industrial processes. All countries will take action in accordance with their national capabilities." [Explanation of symbols]

[0203] 100 Optical components 102 Base material 106 Polymerizable liquid crystal compounds 108 Retardation layer 110 Laminate 200 Optical Components 300 Test Film 302 Photoalignment area 304 Non-photoalignment region 400 Liquid crystal cell structure 410 Liquid crystal layer 420 Alignment film substrate 422 Glass Substrate 424 Orientation Film 500 Rating System 510 1st Polarizing Film 520 2nd Polarizing Film 530 Backlighting 600 Optical Alignment Processing System 610a Xe Excimer Lamp 610b KrCl excimer lamp 610c Deep-UV Lamp 612 Reflector 614 Lamphouse 620a VUV polarizer 620b,620c DUV polarizer 622 Wavelength Selection Filter 630 Shading plate 640 Purge Box 650 Parallel Light Irradiation System 660 Stage

Claims

1. A method for manufacturing an optical member, comprising the steps of: A step of irradiating a substrate having a transmittance of 50% or more with respect to a wavelength used by the optical member with linearly polarized ultraviolet light having a wavelength of 200 nm or less without forming an alignment film, thereby performing an alignment treatment on a surface of the substrate itself; laminating a polymerizable liquid crystal compound on the substrate after the irradiation with the linearly polarized ultraviolet light; forming a retardation layer by aligning the polymerizable liquid crystal compound according to the state of the base material; A manufacturing method comprising:

2. 2. The method according to claim 1, wherein the retardation layer is oriented in a direction parallel to the polarization direction of the linearly polarized ultraviolet light.

3. 3. The method according to claim 1, wherein the photochemical reaction of the substrate induced by the irradiation of the linearly polarized ultraviolet light is a decomposition reaction.

4. 4. The method according to claim 1, wherein the material of the substrate is any one of PET (polyethylene terephthalate), TAC (triacetyl cellulose), and cyclic olefin polymer.

5. 5. The method according to claim 1, wherein the polymerizable liquid crystal compound has anomalous dispersion.

6. 6. The method according to claim 1, wherein the irradiation with the linearly polarized ultraviolet light is performed in an inert gas atmosphere.

7. The substrate is PET, 2. The method according to claim 1, wherein the step of irradiating linearly polarized ultraviolet light irradiates linearly polarized ultraviolet light having a wavelength of 222 nm or 254 nm instead of the linearly polarized ultraviolet light having a wavelength of 200 nm or less.

8. The substrate is PET, 8. The method according to claim 1, wherein the irradiation with the linearly polarized ultraviolet light is performed in an atmosphere containing oxygen.

9. An apparatus for manufacturing an optical member, comprising: A conveying means for conveying a film-like substrate having a transmittance of 50% or more for a wavelength used by the optical member; an illumination device that irradiates the substrate with linearly polarized ultraviolet light having a wavelength of 200 nm or less without forming an alignment film, thereby performing an alignment treatment on the surface of the substrate itself; An apparatus for manufacturing an optical member, comprising:

Citation Information

Patent Citations

  • Phase difference film and method for forming same

    CN101726785A

  • Method for manufacturing wide-band cholesteric liquid crystal film, and circularly polarizing plate

    JP2005345982A

  • Optical element, its manufacturing method, and exposing method

    JP2009086191A

  • Grid polarizing element, method and apparatus for emitting polarized ultraviolet light, method for manufacturing substrate having optical alignment layer and optical alignment device

    JP2015125280A

  • Method for manufacturing retardation plate, laminate with retardation plate, and display device with retardation plate

    JP2016200639A